Digital Vigilantism As A Form Of Political Engagement? A Comparative Approach - Loveluck, Benjamin (AoIR Selected Papers of Internet Research, 2017)
The aim of this paper is to shift attention to forms of public engagement and collective action which can be understood as "digital vigilantism". These involve various instances of "taking the law into your own hands" online, building on the specificities of the digital environment in order to exert forms of direct punishment. Drawing on both digital ethnography and political theory, I will first provide a more precise definition of what is meant by digital vigilantism, and how it relates to other (non-digital) contexts and specifically to the United States political history and political culture. I will then provide several case studies of online vigilantism both in the US and in France, which will serve to illustrate the phenomenon, its many different forms and the “action repertoires” which can be identified. Finally, a series of further questions will be outlined and addressed in order to understand if, indeed, such phenomena qualify as forms of political engagement; and how they question existing institutions – the judicial system, the press, the police – whose role is normally to deal with conflict resolution.